Covid-19 vaccination and chronic urticaria: A paradigm study - Anubha Dev; Apoorva Sharma; Anuradha Bishnoi; Davinder Parsad; Muthu Sendhil Kumaran (Wolters Kluwer Medknow Publications, 2023)
Background: Multiple vaccines were introduced during 2020-2021 to combat Covid-19 pandemic, being one of the successful vaccine programmes in the present era. Very few studies are available on status of chronic urticaria (CU) post Covid-19 vaccination. Aim: The aim of this study was to study effect of Covid-19 vaccination on our urticaria cohort. Materials and Methods: In this retrospective study, case records of CU patients registered in urticaria clinic, who had received any type of Covid-19 vaccine during the interval of March 2021-2022 were retrieved. Patients were classified as 'vaccine induced urticaria' (VIU) when CU developed for first time post-vaccination and 'vaccine exacerbated urticaria' (VEU) when administration of vaccine exacerbated disease activity in previously diagnosed CU. Results: Overall, 353 CU patients registered with us during this period, 265 had received atleast one dose of a Covid-19 vaccine, of which 12 reported VEU (ten of whom had received adenovirus vector vaccine), and three patients were diagnosed with VIU (all had received inactivated virus vaccine). Mean vitamin D3 levels were significantly higher in patients who had VEU as compared to those CU patients without exacerbation (p = 0.003). Significant correlation was observed between level of concern regarding adverse effects of vaccination, pre-vaccination, and post-vaccination urticaria activity score (UAS-7), (Pearson correlation coefficient = 0.66, P = 0.007) in both VEU and VIU. Urticaria symptoms were controlled in 75% and 66.6% patients, respectively, of VEU and VIU, after one month of initiating standard antihistamine treatment. Conclusion: Hence, we conclude that though Covid-19 vaccines can trigger CU, standard treatment protocols control disease activity in most patients.